Unmasking the contributing factors of entrepreneurial activities among men and women in Ghana - Quartey, P.; Danquah, M.; Owusu, G.; Iddrisu, A.M. (Journal of Economic Studies, 2018)
Purpose Using the 2010 Global Entrepreneurship Monitor (GEM) survey data, the purpose of this paper is to investigate the contributing factors of entrepreneurial propensity among males and females in Ghana. Design/methodology/approach Using a measure of entrepreneurial propensity that takes into account individuals who are involved in starting a new business (nascent entrepreneurs) as a dependent variable and socio-demographic characteristics, and perceptual variables as explanatory variables, the study adopts robust empirical estimation techniques to examine how these variables influence the probability of starting a new business among men and women in Ghana. Findings The probability of being a male nascent entrepreneur is significantly dependent upon a wide range of factors including demographic, economic, perceptual and contextual elements, albeit with important variations across gender. An individuals’ subjective assessment of fear of failure in starting a business and of having the requisite entrepreneurial capabilities; the age of the individual; gender of the individual; work status and contextual factors matters for entrepreneurial propensity in Ghana. However, important differences exist in the drivers of entrepreneurial propensity for males and females with females’ entrepreneurship attributed largely to conditions of necessity relative to their male counterparts. Originality/value The main value of this paper is to use the GEM survey (which is nationally representative) for Ghana to analyze the contributing factors of the entrepreneurial propensity among men and women in Ghana.
Keywords: Entrepreneurial activity; Ghana; Perceptual variables; Socio-demographic factors